Electroweak measurements at the LHC and HL-LHC with ATLAS and CMS - Magnan Anne-Marie (EPJ Web of Conferences)
This contribution aims at giving an overview of ATLAS and CMS results in the electroweak sector of the standard model. First, the latest precision measurements for a selection of standard model parameters of the electroweak sector will be reviewed. Then, measurements related to the electroweak production of vector bosons with two jets, and inclusive diboson production, both class of processes sensitive to anomalous triple gauge couplings, will be summarised. A review of the measurements available for vector boson scattering and triboson processes will follow, both class of processes sensitive to anomalous quartic gauge couplings. Finally, the limits on anomalous couplings will be summarised. The review covers both LHC and HL-LHC (ATLAS and CMS) results.